Prevalence and awareness of text neck syndrome and text thumb syndrome in young adult population - B, Senthil Kumar; Khaleeluddin, Kouser Banu; Jayakumar, Saikarthick; K, Ezhil Vendhan (Journal of Applied Pharmaceutical Research, 2024)
Background: The term "text neck" can be defined as repetitive strain injury and pain due to excessive viewing and texting on a smartphone for a prolonged duration. Long-term untreated text neck results in inflammation of ligaments and muscles, which can lead to permanent arthritic changes. Many smart phone users experience thumb/wrist pain, but some people who develop pain are smart phone addicts. The present study checks the prevalence and awareness of text neck and thumb text syndrome in young adults. Methods: A cross-sectional study was conducted with 200 volunteers between 18-25 years age who have been using mobile phone in the last 5 years. A structured questionnaire was created, validated, and used for the study. Descriptive statistics was used to assess responses received from participants. The prevalence of text neck syndrome and thumb text syndrome has been established. Results: About 50.3% of the participants were unaware of text neck syndrome and 57.1% of text thumb syndrome. Maximum mobile phone usage included texting and calls. About 45.2% of the participants use their right thumb and index finger to text. 33% of people have a head forward posture when using mobile phones. An analysis of pain, discomfort, and duration during mobile phone use was done and will be presented at a forum. Conclusion: The prevalence of text neck and thumb text syndrome in the young adult population indicates the need to plan future pain management strategies and increase user awareness